(Re)defining resilience: how engineering educators understand and teach resilience - Wint, Natalie (2024)
Background: In recent years “resilience” has become framed as a positive attribute, contributing to student success within higher education (HE). The need for students to develop and demonstrate resilience seems pertinent within engineering degrees which are often associated with heavy workloads, high rates of attrition and increased mental health issues. Secondly, engineering degrees prepare students for a profession, and likely place emphasis on graduate attributes such as resilience. Finally, the rate of technological advancement and societal change places additional demands on graduates to adapt to career changes. Purpose/Hypothesis: Despite emphasis on the benefits of demonstrating resilience, there is a lack of research focusing on how it is understood and taught within engineering education. In this work we seek to understand how engineering educators conceptualize resilience, whether they feel responsibility to help students develop resilience, and their approach to this. Design/Method: Data was collected via semi-structured interviews with thirteen individuals from two UK based universities. Transcripts were analyzed using reflexive thematic analysis (RTA). Results: Although resilience is considered a desirable attribute for engineering graduates, this work highlights differences in the degree to which educators feel responsible for its development, as well as methods which they may adopt. The significant variation in the way the term is conceptualized (being associated with adaptability, as well as resistance to change) has several implications for intervention design. Conclusion: Given emphasis on both resilience and student mental health within HE discourse, there is a need for institutions, as well as employers, to provide strong messaging regarding what is meant by the term and how they believe it presents as an attribute of engineering graduates. There should also be sustained, intentional efforts to stop the use of deficit-based language and approaches which fail to recognize wider structural inequalities that exist within institutions and the engineering profession more widely.